(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to identify the size of the effect of employing artificial intelligence on the achievement of the students of the Department of Art Education in the subject of Communication and Informatics The researcher chose the research sample in a random manner and it consisted of (70) distributed between two classrooms. Hall (1) represented the experimental group, with (35) male and female students, and Hall (4) represented the control group, with (35) male and female students. The researcher adopted an experimental design with partial control for two groups (experimental and control) with pre- and post-tests The two research groups were rewarded with variables (chronological age, intelligence, previous experience), and the researcher prepared the research tool (the achievement test), which is the pre-test, which is the same as the post-test, consisting of (32) multiple-choice items with four alternatives. The validity and reliability were verified, and the difficulty coefficient, discriminatory power, and effectiveness of the wrong alternatives to the test were calculated. The experiment began on Monday, corresponding to (07/10/2024) for the two research groups (experimental and control) and ended on Monday, corresponding to (11/11/2024) After completing the correction, the t-test and the Eta square U2 were used to verify the significance of the differences between the two groups. The results reached by the researcher showed the superiority of the experimental group over the control group.